2009
DOI: 10.1002/pmic.200800266
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Brucella suis under oxygen deficiency reveals flexibility in adaptive expression of various pathways

Abstract: Low oxygen tension was proposed to be one of the environmental parameters characteristic of the patho-physiological conditions of natural infections by Brucella suis. We previously showed that various respiratory pathways may be used by B. suis in response to microaerobiosis and anaerobiosis. Here, we compare the whole proteome of B. suis exposed to such low-oxygenated conditions to that obtained from bacteria grown under ambient air using 2-D DIGE. Data showed that the reduction of basal metabolism was in lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…The analysis of the intramacrophagic virulome of Brucella suis showed that low levels of nutrients and oxygen are major features of its replicative niche (19). A recent proteomic study has shown that Brucella adapts to low-oxygen conditions intracellularly by upregulating glycolysis and denitrification (1). Most of the upregulated proteins were involved in energy metabolism, such as transketolase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and glycerol-3-phosphate ABC transporter.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the intramacrophagic virulome of Brucella suis showed that low levels of nutrients and oxygen are major features of its replicative niche (19). A recent proteomic study has shown that Brucella adapts to low-oxygen conditions intracellularly by upregulating glycolysis and denitrification (1). Most of the upregulated proteins were involved in energy metabolism, such as transketolase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and glycerol-3-phosphate ABC transporter.…”
Section: Discussionmentioning
confidence: 99%
“…In R. sphaeroides , such analyses revealed that PrrA (RegA) regulates as a “master controller” directly or indirectly ~25% of the genes (Eraso et al, 2008). In the case of B. suis , we demonstrated that under low oxygen tension, the bacteria reduce their basal metabolism as growth decreases or stops and activate glycolysis and denitrification to maintain energy production (Al Dahouk et al, 2009). According to these results, we correctly predicted numerous systems under the control of RegA and potentially needed for persistence, which will contribute to give an insight into the mechanisms enabling B. suis to set up persistence.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies (10,11,12), we demonstrated that B. suis is able to use various systems to adapt to oxygen-limited conditions, in vitro as well as inside the host organism. The flexibility of this bacterium with respect to oxygen depletion is actually very high since it can grow under low oxygen concentrations (10) and survive under anaerobic denitrifying conditions (13) without repression of basic metabolic activities, as shown by our proteomic analysis (12).…”
mentioning
confidence: 99%
“…In previous studies (10,11,12), we demonstrated that B. suis is able to use various systems to adapt to oxygen-limited conditions, in vitro as well as inside the host organism. The flexibility of this bacterium with respect to oxygen depletion is actually very high since it can grow under low oxygen concentrations (10) and survive under anaerobic denitrifying conditions (13) without repression of basic metabolic activities, as shown by our proteomic analysis (12). This was therefore in accordance with an earlier classification of several alphaproteobacteria, which distinguished B. melitensis (14) as a bacterium with an expected facultative/aerobic lifestyle, according to its rank 1 position with respect to the number of predicted highly expressed genes of different energy metabolism pathways, denitrification included.…”
mentioning
confidence: 99%